2010
DOI: 10.2353/ajpath.2010.090781
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Interleukin-6 Expression in Human Decidual Cells and Its Potential Role in Chorioamnionitis

Abstract: Chorioamnionitis frequently precedes both genital tract and placental inflammation and is both a primary cause of maternal morbidity and a major antecedent of preterm premature rupture of the membranes (PPROM) as well as preterm delivery (PTD). In most cases of chorioamnionitis , neutrophils dominate the decidua. In a subset of these cases , a predominance of monocytes is uniquely associated with both neonatal intraventricular hemorrhage and death. The multifunctional cytokine , interleukin-6 , promotes local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 53 publications
(56 reference statements)
2
50
0
2
Order By: Relevance
“…This is in agreement with previous reports showing that IL-6 is secreted by decidual cells under non-infectious conditions [32,33], chorioamnionitis [34], and decidual primary cultures from women who underwent preterm labor with subclinical intrauterine infection [25,35]. Although it has been described that E 2 and P 4 downregulate some inflammatory markers in different cell types [25], in our model, decidual IL-6 secretion was not depleted by hormones as it was previously reported by Lockwood et al [34]. This discrepancy may be due to differences in hormone concentration and/or decidualization time.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is in agreement with previous reports showing that IL-6 is secreted by decidual cells under non-infectious conditions [32,33], chorioamnionitis [34], and decidual primary cultures from women who underwent preterm labor with subclinical intrauterine infection [25,35]. Although it has been described that E 2 and P 4 downregulate some inflammatory markers in different cell types [25], in our model, decidual IL-6 secretion was not depleted by hormones as it was previously reported by Lockwood et al [34]. This discrepancy may be due to differences in hormone concentration and/or decidualization time.…”
Section: Discussionsupporting
confidence: 83%
“…This discrepancy may be due to differences in hormone concentration and/or decidualization time. In the same work, the addition of the pro-inflammatory cytokine IL-1β to hormonal-stimulated decidual cells results in enhanced secretion of IL-6 [34], but apparently in our model, IL-6 secretion is not dependent of IL-1β, because our experiments show that IL-1β is not secreted even under infection conditions. However, in our model, the presence of GBS as inflammatory stimulus triggers IL-6 production in DSCs, suggesting a leading role of this cytokine in the pro-inflammatory network elicited by gestational tissues during intrauterine infection.…”
Section: Discussionmentioning
confidence: 64%
“…Other studies have demonstrated high levels of production of IL6 by BeWo cells and its involvement in the endocrine properties of these cells [22,72]. However, this cytokine should be at adequate concentrations at the maternal-fetal interface because high levels of IL6 are associated with preeclampsia and inflammatory processes in the amnion [73,74]. Thus, it is plausible that TGFB1 and IL10 down-modulate IL6 release in order to control the level of this cytokine in BeWo cells, which in turn, promotes the increased proliferation of T. gondii, allowing dissemination of the infection in our model.…”
Section: Discussionmentioning
confidence: 93%
“…Studies genotyping the amniochorion neutrophils demonstrated that the initial inflammatory response is maternal in its origin [ 19, 20, 21 ]. It remains unknown why the initial wave of decidual inflammation [ 22 ] is not associated with signs and symptoms of maternal clinical chorioamnionitis (i.e. fever, maternal leukocytosis).…”
Section: Discussionmentioning
confidence: 99%